Confined Pt11+ Water Clusters in a MOF Catalyze the Low‐Temperature Water–Gas Shift Reaction with both CO2 Oxygen Atoms Coming from Water. Issue 52 (27th November 2018) - Rivero‐Crespo, Miguel A.; Mon, Marta; Ferrando‐Soria, Jesús; Lopes, Christian W.; Boronat, Mercedes; Leyva‐Pérez, Antonio; Corma, Avelino; Hernández‐Garrido, Juan C.; López‐Haro, Miguel; Calvino, Jose J.; Ramos‐Fernandez, Enrique V.; Armentano, Donatella; et al.
Abstract: The synthesis and reactivity of single metal atoms in a low‐valence state bound to just water, rather than to organic ligands or surfaces, is a major experimental challenge. Herein, we show a gram‐scale wet synthesis of Pt1 1+ stabilized in a confined space by a crystallographically well‐defined first water sphere, and with a second coordination sphere linked to a metal–organic framework (MOF) through electrostatic and H‐bonding interactions. The role of the water cluster is not only isolating and stabilizing the Pt atoms, but also regulating the charge of the metal and the adsorption of reactants. This is shown for the low‐temperature water–gas shift reaction (WGSR: CO + H2 O → CO2 + H2 ), where both metal coordinated and H‐bonded water molecules trigger a double water attack mechanism to CO and give CO2 with both oxygen atoms coming from water. The stabilized Pt 1+ single sites allow performing the WGSR at temperatures as low as 50 °C. Abstract : Water do : A catalyst with Pt1 1+ exclusively coordinated to H2 O molecules can be prepared on a gram scale within a metal–organic framework (MOF). It transfers two H2 O molecules to CO and gives, very efficiently, CO2 and H2 (water–gas shift reaction) at 50–150 °C.